Increased proteasome activator 28 gamma (PA28γ) levels are unspecific but correlate with disease activity in rheumatoid arthritis - Gruner, Melanie (BMC Musculoskelet Disord, 2014)
BACKGROUND: PA28γ (also known as Ki, REG gamma, PMSE3), a member of the ubiquitin-and ATP-independent proteasome activator family 11S, has been proved to show proteasome-dependent and -independent effects on several proteins including tumor suppressor p53, cyclin-dependent kinase inhibitor p21 and steroid receptor co-activator 3 (SCR-3). Interestingly, PA28γ is overexpressed in pathological tissue of various cancers affecting e. g. breast, bowl and thyroids. Furthermore, anti-PA28γ autoantibodies have been linked to several autoimmune disorders. The aim of this study was to develop and evaluate a novel and sensitive PA28γ sandwich ELISA for the quantification of PA28γ serum levels in patients with cancer and autoimmune diseases for diagnostic and prognostic purposes. METHODS: PA28γ-specific polyclonal antibodies and recombinant His-tagged PA28γ were purified and used to develop a sandwich ELISA for the detection of circulating PA28γ. With this new assay, PA28γ serum levels of patients with various cancers, rheumatoid arthritis (RA), Sjögren’s syndrome (SS), adult-onset Still’s disease (AOSD) and different connective-tissue diseases (CTD) were compared with healthy control subjects. Anti-PA28γ autoantibodies were additionally confirmed using a newly developed microbead assay. RESULTS: The developed PA28γ sandwich ELISA showed a high specificity with a detection limit of 3 ng/ml. A significant up-regulation of circulating PA28γ was detected in the sera of patients with cancer, RA, SS and CTD. A significant correlation was observed dependent on age as well as anti-PA28γ autoantibody levels with circulating PA28γ protein levels. Furthermore, PA28γ serum levels showed a correlation with disease activity in patients with RA under treatment with the T-cell directed biological compound abatacept according to disease activity score 28 (DAS28) and erythrocyte sedimentation rate (ESR). CONCLUSION: The application of PA28γ as a novel biomarker for diagnostic purposes of a specific disease is limited, since elevated levels were observed in different disorders. However, the correlation with disease activity in patients with RA suggests a prognostic value, which needs to be addressed by further studies. Therefore our results show that PA28γ is a useful marker which should be included in studies related to novel treatments, e.g. abatacept. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2474-15-414) contains supplementary material, which is available to authorized users.